DESCRIPTION OF DISEASES SUFFERED BY MOTHERS AND CHILDREN AT THE AGE OF 0-3 YEARS WITH HEARING LOSS AT MARGONO SOEKARJO PURWOKERTO HOSPITAL - Fahrizal, Eky Danu; Kusdaryanto, Wahyu Dwi; Nafiisah, Nafiisah; Agustina, Nenden Nursyamsi; Darmawan, Anton Budhi (Fakultas Kedokteran Universitas Jenderal Soedirman, 2024)
Hearing loss is difficult to detect in infants and children. It can inhibit cognitive, emotional, language, and communication development. Therefore, hearing loss needs to be immediately examined to minimize its impacts. It is essential to recognize the disease suffered by infants and children, especially those with a history of hearing loss during the pranatal, perinatal, and postnatal periods for early examinations. This study aimed to evaluate diseases characteristic suffered by children with hearing loss aged 0-3 years at RSUD Margono Soekarjo, Purwokerto. This research was descriptive, using secondary data. The analysis used was univariate. Hearing loss in children during; the pranatal (15.4%) could be caused by a family history of the disease, TORCH infection, and preeclampsia; during the perinatal (70,3%) could be caused by low birth weight, prematurity, hyperbilirubinemia, and neonatal asphyxia, and; during the postnatal period (14.3%) could be caused by the use of mechanical ventilators and febrile seizures. The disease character in children aged 0-3 years with hearing loss at RSUD Margono Soekarjo Purwokerto are disease during pranatal, perinatal, and postnatal periods